110 Answering the Call for Greater LGBTQ+ Research Inclusivity by Co-Developing A Workshop for Researchers - Gelise Thomas; Lizzie Bjork; Zina Hempstead; Gulnar Feerasta (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: The objectives of this workshop were to: (1) provide learners with a space to become aware of and discuss the history of the LGBTQ+ community in medical and public health research; (2) apply frameworks for LGBTQ+ inclusivity in research, inspired by lived experience and multimedia; and (3) assess LGBTQ+ research inclusivity best practices. METHODS/STUDY POPULATION: The CTSC provided the LGBT Community Center of Greater Cleveland (Center) with access to academic resources via an affiliate account and insights on the clinical and translational science research process. Members of the CTSC Research Equity, Accessibility, Diversity, and Inclusion team met regularly with the education and programming team at the Center to review research findings for workshop segments, ideate and provide feedback on activities, and strategize to ensure a psychologically safe virtual environment for learners. Zoom registration was used for workshop registration. An evaluation survey, created by the LGBT Community Center of Greater Cleveland (Center), was deployed by the CTSC to learners after the workshop. Respondents reported that the LGBTQ+ terminology focus was most valuable. RESULTS/ANTICIPATED RESULTS: To maximize investment in and scale theLGBTQ+ Inclusivity For Researchers workshop, the LGBT Community Center of Greater Cleveland offered a shortened version to their Youth Participatory Action Research group and will continue to offer the workshop in their suite of program/educational offerings. The CTSC plans to offer opportunities to co-host the workshop at its hospital system partner institutions, with room to tailor content based on internal LGBT resources (e.g., gender care offered at the institution). We hope to see a remarkable increase in LGBTQ+ identifying researchers, LGBTQ+ participation in research studies and clinical trials, and LGBTQ+ research topics/ideas/questions in response to CTSC pilots, local, national, and global funding opportunities. DISCUSSION/SIGNIFICANCE: LGBTQ+ people are less likely to have a regular health care provider—impeding screening, diagnosis, and treatment. This is reflected in health research where clinical research participation may follow a diagnosis. By providing tools for LGBTQ+ research inclusion, we will catalyze more research with LGBTQ+ people—as researchers and participants.